Cytogenetic studies in four cultivated Amaranthus (Amaranthaceae) species - Bonasora, Marisa Graciela (2013)
Fil: Bonasora, Marisa Graciela. Universidad de Buenos Aires. Facultad de Agronomía. Cátedra de Botánica Agrícola. Buenos Aires, Argentina.